Effect of electron beam irradiation (EB) on gas barrier property of HDPE/EPDM nanocomposites - Jamal, Nur Ayuni; Anuar, Hazleen; Abd Razak, Shamsul Bahri (Trans Tech Publications, Switzerland, 2011)
In this study, electron beam irradiated (EB) was applied as a crosslinker agent for both pristine high density polyethylene (HDPE) and HDPE/ ethylene propylene diene monomer (EPDM)nanocomposite systems. The doses rate for EB irradiated technique were varied between 50, 100,150 and 200 kGy. The nanocomposites systems were first prepared via melt intercalation method with different organophilic montmorillonite (OMMT) loadings. It was found that, with 4 vol% organophilic montmorillonite (OMMT) loading, the barrier resistance of nanocomposite against oxygen transmission was significantly enhanced by EB irradiation dose rate of 100 kGy. The oxygen transmission for nanocomposite was reduced by 23.48%. The interplanar spacing,spacings of OMMT in nanocomposites were monitored using x-ray diffraction (XRD) and the extent of delamination was examined by transmission electron microscope (TEM). The wide angle of XRD patterns showed the increased interplanar spacing, of clay layers, indicating enhanced compatibility between polymer matrix and OMMT with EB irradiation. TEM photomicrographs illustrated the mixed intercalated and partial exfoliated structures of the nanocomposites with the irradiation process.